Accelerated Healing of The Wider Lateral Defects in Adult Cleft Palate Repairs - Mukarramah, Dewi Aisyah; Sudjatmiko, Gentur (Jurnal Plastik Rekonstruksi, 2012)
Background: Adult primary palatoplasty is more challenging tha n in infants because the gaps are wider. The risk ofintraoperative bleeding and palatal fistula are higher. Most adults with un-operated palatal cleft have good maxillary growth but poor speech. The aim of this study is to introduce our technique in repairing wide cleft palate in adult patients. Patients and Methods: We report four patients with cleft palate who underwent palatoplasty at adulthood. The age ranges from 17 to 20 years. Interspina distance were between 2 to 3.5 cm. All of them were nonsyndromic and had normal maxillary growth. The surgical technique used on these patients was two-flap palatoplasty with an additional 3 mm gingival bulk on the lateral side of the flap. Honey was given as oral drops postoperatively. Result: Lateral palatal defect healed well and epithelialized completely between 7 -14 days postoperative and only one small palatal fistula was found with this modified technique. All subjects had good maxillary growth, and speech outcome was poor to begin with.Summary: Two-flap palatoplasty can adequately provide palatal closure, especially with an additional lateral flap extension to include gingival components. This extension widens the flaps and aid palatal closure by not leaving lateral defects too wide.